Microplastics in plastic bottle recycling and textile manufacturing wastewater: characterization and removal using ultrafiltration membranes - Q. N. Siew; W. J. Lau; S. Sethupathi; L. C. Sim; J.-J. Jiang; S. O. Lai; S. H. Shuit; G. Issabayeva; W. C. Chong (International Journal of Environmental Science and Technology, 2026)

Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Comparison of phenotypic methods and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry for the identification of aero-tolerant Actinomyces spp. isolated from soft-tissue infections - L. S. Y. Ng; J. H. C. Sim; L. C. Eng; S. Menon; T. Y. Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)